Health Care Waste Management and COVID 19 Pandemic Policy, Implementation Status and Vaccine Management - Ghosh, Sadhan Kumar; Agamuthu, Pariatamby (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book deals with the general principles, policy instruments, sustainability of supply chain, and business of health-care waste (HCW) management including inputs on exercise in immune health defense against COVID 19. Health-care waste management is very important in any country for protection of environmental and animal and human health. The COVID-19 pandemic, in addition, has augmented this importance to a greater extent. Italy has been successful in curbing the problems related to HCW management during the COVID-19 pandemic at very fast rates from the worst situation, while for a few countries in Asia and Africa, challenges still exist. It is necessary that policy makers, researchers, and implementers gain more knowledge and information on these aspects and improve the strategies and actions. Addressing these issues will reduce the cost of health care as well as resource inefficiency hindering sustainable development goals. This book is of interest and useful to practitioners, capacity builders and policy makers, entrepreneurs, NGOs, and general people, and is a valuable source of reference to the relevant researchers and students in global markets. The book serves as a reading material for undergraduate and graduate students of environmental science, waste management, and medical science. National and international scientists as well as policy makers will also find this to be a useful read. .
Part 1 COVID 19 Waste Management & cultural perspectives -- Chapter 1 Waste Management during pandemic of COVID 19 in India, Italy and USA-the influence of cultural perspectives -- Part 2 Health Care Waste Management and Case studies -- Chapter 2 Clinical Waste Management In Malaysia And Covid-19 Waste Management Case Study -- Chapter 3 Waste Management related to COVID-19 in the Noncontact Era: Case Study of the Republic of Korea -- Chapter 4 Healthcare Waste Management and Post Pandemic Countermeasures: The Case of the Philippines -- Chapter 5 Bio medical waste management & Case Study in India -- Part 3 Management of Non-medical waste infected by SARS-CoV-2 -- Chapter 6 The immediate Italian response to the management of non-medical waste potentially infected by SARS-CoV-2 during the emergency phase of the pandemic -- Part 4 Health Care Waste Management during Pre- and post-COVID-19 scenario -- Chapter 7 Overview of Infectious Healthcare Waste Management in Thailand in pre - and - during COVID-19 Context -- Chapter 8 Health Care waste management in Nepal: Pre- and post-COVID-19 scenario -- Part 5 COVID-19 Healthcare Waste Management in 3R Perspective -- Chapter 9 COVID-19 and Healthcare Waste Management (HCWM) in Myanmar: Perspectives from the Triple R (Response, Recovery and Redesign) -- Part 6 Healthcare Waste Management & Impact of COVID-19 -- Chapter 10 Health Care Waste Management Practices in Nigeria: A Review -- Chapter 11 Medical Waste Management in Lebanon and Impact of Covid-19 -- Part 7 Global picture of Covid-19 -- Chapter 12 Global picture of Covid-19 pandemic with emphasis on European Subcontinent -- Part 8 Preventive Measures to indirectly reduce COVID 19 Waste generation - Vaccination and Rehabilitation -- Chapter 13 COVID-19 Vaccination in India -- Chapter 14 VACCINATION FOR THE COVID-19 PANDEMIC -- Chapter 15 Exercise in Immune Health Management and Rehabilitation against COVID-19. .
Keywords: Refuse and refuse disposal; Environmental health; Environmental management; Environmental engineering; Biotechnology; Bioremediation; Waste Management/Waste Technology; Environmental Health; Environmental Management; Environmental Engineering/Biotechnology.